RECOVERY OF CARBON FIBER FROM CARBON FIBER REINFORCED POLYMER WASTE VIA PYROLYSIS - Yatim, N.M.; Shamsudin, Z.; Shaaban, A.; Ghafar, J.A.; Khan, M.J.H. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
The increasing use of carbon fiber reinforced polymer (CFRP) in high end application industry needs for recycling technique to recover the valuable carbon fibers, reduce the waste produced and provide a closed loop for this material. Most CFRP waste have been disposed of in landfills after their expiration of service life, generating environmental problems and potential release of toxic byproducts. This paper examines the recovery of carbon fibers (rCF) via pyrolysis technique by particularly studied the influence of different atmosphere (nitrogen and combination of nitrogen and oxygen) and final heating temperature (550°C, 600°C and 650°C). Pyrolysis held under an inert atmosphere of nitrogen at the heating temperature range from 250 to 420⁰C was found significance to decompose epoxy resin components. While oxygen atmosphere at higher heating temperature was found needed to achieve a complete elimination of resin from rCF. Pyrolysis at low temperature (550°C) revealed rCF production with clean and uniform spherical shape. Thermogravimetric analysis (TGA) reveal 540°C as final heating temperature that efficiently recover CF. Morphological and structural examination of the rCF was performed via SEM and Raman spectroscopy respectively. The specific heating profile of pyrolysis technique is present to recover valuable CF from complex CFRP.